Critical Role of Dynamic Flexibility in Ge‐Containing Zeolites: Impact on Diffusion. Issue 29 (15th June 2016) - Gutiérrez‐Sevillano, Juan José; Calero, Sofía; Hamad, Said; Grau‐Crespo, Ricardo; Rey, Fernando; Valencia, Susana; Palomino, Miguel; Balestra, Salvador R. G.; Ruiz‐Salvador, A. Rabdel
Abstract: Incorporation of germanium in zeolites is well known to confer static flexibility to their framework, by stabilizing the formation of small rings. In this work, we show that the flexibility associated to Ge atoms in zeolites goes beyond this static effect, manifesting also a clear dynamic nature, in the sense that it leads to enhanced molecular diffusion. Our study combines experimental and theoretical methods providing evidence for this effect, which has not been described previously, as well as a rationalization for it, based on atomistic grounds. We have used both pure‐silica and silico‐germanate ITQ‐29 (LTA topology) zeolites as a case study. Based on our simulations, we identify the flexibility associated to the pore breathing‐like behavior induced by the Ge atoms, as the key factor leading to the enhanced diffusion observed experimentally in Ge‐containing zeolites. Abstract : Ge force : Incorporation of germanium in zeolites is well known to confer static flexibility to their framework by stabilizing the formation of small rings. In this work, it is shown that this flexibility goes beyond this static effect, and also manifests a clear dynamic nature (see figure), in the sense that the higher window flexibility leads to enhanced molecular diffusion.